Insights into group-specific pattern of secondary metabolite gene cluster in Burkholderia genus - Kim, Byeollee; Han, So-Ra; Lee, Hyun; Oh, Tae-Jin (Frontiers in Microbiology, 2024)
Burkholderia is a versatile strain that has expanded into several genera. It has been steadily reported that genome features of Burkholderia exhibit activities ranging from plant growth-promoting to pathogenicity across various isolation areas. The objective of this study was to investigate secondary metabolite patterns of 366 Burkholderia species through comparative genomics. Samples were selected based on assembly quality assessment and similarity below 80% in average nucleotide identity. Duplicate samples were excluded. Samples were well divided into two groups using FastANI analysis. Group A included B. pseudomallei complex. Group B included B. cepacia complex. Limitation of MLST was proposed. Detection of genes, including environmental and virulence-related genes, was performed. In pan-genome analysis, each complex possessed a similar pattern of cluster of orthologous groups. Group A (n = 185) had 14,066 cloud genes, 2,465 shell genes, 682 soft-core genes, and 2,553 strict-core genes. Group B (n = 181) had 39,867 cloud genes, 4,986 shell genes, 324 soft-core genes, 222 core genes, and 2,949 strict-core genes. To analyze biosynthetic gene cluster (BGC), antiSMASH was employed. Subsequently, results were utilized for network analysis using BiG-SCAPE and CORASON. Principal component analysis was conducted and a table was constructed using results obtained from antiSMASH. Results showed that divided into group A and group B. It is expected that various species show similar patterns of secondary metabolite gene clusters. For in-depth analysis, a network analysis of secondary metabolite gene clusters was conducted, exemplified by BiG-SCAPE analysis. Depending on the species and complex, Burkholderia possessed several kinds of siderophore. Among them, ornibactin was possessed in most of Burkholderia and was clustered into 4062 clans. It revealed that a similar pattern of gene clusters depending on the species. NRPS_04014 belonged to siderophore BGCs including ornibactin and indigoidine. However, it was observed that each family included similar species. This suggests that, besides siderophores being species-specific, the ornibactin gene cluster itself might also be species-specific. We suggest that siderophore are associated with environmental adaptation, possessing a similar pattern of siderophore gene clusters among species could provide another perspective on species-specific environmental adaptation mechanisms.